The voltage-gated potassium channel KV1.3 regulates neutrophil recruitment during inflammation. Issue 5 (21st April 2021) - Immler, Roland; Nadolni, Wiebke; Bertsch, Annika; Morikis, Vasilios; Rohwedder, Ina; Masgrau-Alsina, Sergi; Schroll, Tobias; Yevtushenko, Anna; Soehnlein, Oliver; Moser, Markus; Gudermann, Thomas; Barnea, Eytan R; et al.
Abstract: Aims: Neutrophil trafficking within the vasculature strongly relies on intracellular calcium signalling. Sustained Ca 2+ influx into the cell requires a compensatory efflux of potassium to maintain membrane potential. Here, we aimed to investigate whether the voltage-gated potassium channel KV 1.3 regulates neutrophil function during the acute inflammatory process by affecting sustained Ca 2+ signalling. Methods and results: Using in vitro assays and electrophysiological techniques, we show that KV 1.3 is functionally expressed in human neutrophils regulating sustained store-operated Ca 2+ entry through membrane potential stabilizing K + efflux. Inhibition of KV 1.3 on neutrophils by the specific inhibitor 5-(4-Phenoxybutoxy)psoralen (PAP-1) impaired intracellular Ca 2+ signalling, thereby preventing cellular spreading, adhesion strengthening, and appropriate crawling under flow conditions in vitro . Using intravital microscopy, we show that pharmacological blockade or genetic deletion of KV 1.3 in mice decreased neutrophil adhesion in a blood flow dependent fashion in inflamed cremaster muscle venules. Furthermore, we identified KV 1.3 as a critical component for neutrophil extravasation into the inflamed peritoneal cavity. Finally, we also revealed impaired phagocytosis of Escherichia coli particles by neutrophils in the absence of KV 1.3. Conclusion: We show that the voltage-gated potassium channel KV 1.3 is critical for Ca 2+ signalling and neutrophil trafficking during acute inflammatory processes. Our findings do not only provide evidence for a role of KV 1.3 for sustained calcium signalling in neutrophils affecting key functions of these cells, they also open up new therapeutic approaches to treat inflammatory disorders characterized by overwhelming neutrophil infiltration. Graphical Abstract: